Bertie : the complete Prince of Wales mysteries - Lovesey, Peter (Soho Crime, 2019)
"The Complete Prince of Wales Mysteries collects all three of Peter Lovesey's charming and thrilling Bertie adventures in a single volume for the first time. Albert Edward, Prince of Wales--Bertie, as he's known--is the eldest son of Queen Victoria and future King Edward VII. Bertie is a pleasure seeker, always searching out the best meals, the most beautiful women, and the most lavish parties. As Prince Regent, Bertie is expected to behave like a proper royal and avoid scandal. Instead, his love of excitement leads him to a decidedly unprincely hobby: sleuthing. Bertie is not the best detective, but that does not stop him from trying to solve every case that crosses his path, including the feverish suicide of the greatest jockey of the century, the mysterious death of a member of the royal hunting party, and the murder of the son-in-law of an old friend"--